Geburts: Arien: Mädchenprozession - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1994)
GEBURTS-ARIEN / BIRTH -ARIAS of MONDAY from LIGHTfor 3 sopranos, 3 tenors / choir / children's voices / modern orchestraMÄDCHENPROZESSION / GIRLS' PROCESSION 1st version for girls' choir a cappella and pianoMADCHENPROZESSION 2nd version for girls' choir, piano / choir /modern orchestra, sound scenes